2022
DOI: 10.3389/fimmu.2022.989298
|View full text |Cite
|
Sign up to set email alerts
|

Multiple functions of heterogeneous nuclear ribonucleoproteins in the positive single-stranded RNA virus life cycle

Abstract: The heterogeneous nuclear ribonucleoproteins (hnRNPs) are a diverse family of RNA binding proteins that are implicated in RNA metabolism, such as alternative splicing, mRNA stabilization and translational regulation. According to their different cellular localization, hnRNPs display multiple functions. Most hnRNPs were predominantly located in the nucleus, but some of them could redistribute to the cytoplasm during virus infection. HnRNPs consist of different domains and motifs that enable these proteins to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 164 publications
0
19
0
Order By: Relevance
“…hnRNPs have been reported to undergo various posttranslational modifications (PTMs), such as phosphorylation, glycosylation, s-nitrosylation, methylation, acetylation, ubiquitination, and SUMOylation. These PTMs are essential for cellular localization, protein-protein interactions, and nucleic acid binding of hnRNPs, in addition to regulating viral RNA processing and virus replication (29)(30)(31). Some hnRNPs are strictly nuclear [e.g., hnRNP C and U (32)], whereas others remain associated with the mRNA as it passes through nuclear pores and therefore undergo constant nucleocytoplasmic movement (e.g., members of hnRNP A, B, E, D, I, and K group) (12).…”
Section: Structure and Function Of Hnrnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…hnRNPs have been reported to undergo various posttranslational modifications (PTMs), such as phosphorylation, glycosylation, s-nitrosylation, methylation, acetylation, ubiquitination, and SUMOylation. These PTMs are essential for cellular localization, protein-protein interactions, and nucleic acid binding of hnRNPs, in addition to regulating viral RNA processing and virus replication (29)(30)(31). Some hnRNPs are strictly nuclear [e.g., hnRNP C and U (32)], whereas others remain associated with the mRNA as it passes through nuclear pores and therefore undergo constant nucleocytoplasmic movement (e.g., members of hnRNP A, B, E, D, I, and K group) (12).…”
Section: Structure and Function Of Hnrnpsmentioning
confidence: 99%
“…The hnRNPs are considered as one of the most important RBPs family for the functions in the viral life cycle (50). Several members of the hnRNP family form functional complexes with viral RNAs and proteins (31). A study on proteome-wide scale analysis of viral RNA-host cell interaction identified 12 hnRNPs in the core vRNA interactome, which makes these proteins usual suspects in vRNA interactome analysis (51).…”
Section: The Roles Of Hnrnps In the Virus Life Cyclementioning
confidence: 99%
“…This indicates a complex cooperative mechanism between YTHDF proteins 41 . Other reader proteins that can identify the m 6 A motif include the heterogeneous nuclear ribonucleoproteins (hnRNP) family (hnRNPA2B1, hnRNPC, and hnRNPG) 42 , 43 and insulin-like growth factor 2 mRNA-binding proteins (IGF2BPs, including IGF2BP1/2/3) 44 , 45 (Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous nuclear ribonucleoproteins (hnRNPs) are a group of host RNA-binding proteins that have been reported to promote or suppress virus replication [ 1 ]. As antiviral factors, hnRNPAB and hnRNPA2/B1 respectively interact with nucleoprotein (NP) and nonstructural protein 1 (NS1) of influenza A virus to restrict viral mRNA nuclear export, thus inhibiting viral replication [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%